2022
DOI: 10.1002/smll.202200073
|View full text |Cite
|
Sign up to set email alerts
|

Enabling High Loading in Single‐Atom Catalysts on Bare Substrate with Chemical Scissors by Saturating the Anchoring Sites

Abstract: Atomically dispersed metal catalysts often exhibit high catalytic performances, but the metal loading density must be kept low to avoid the formation of metal nanoparticles, making it difficult to improve the overall activity. Diverse strategies based on creating more anchoring sites (ASs) have been adopted to elevate the loading density. One problem of such traditional methods is that the single atoms always gather together before the saturation of all ASs. Here, a chemical scissors strategy is developed by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Reproduced from Ref. [52] with permission from the American Chemical Society. Scheme for the construction of high-loading single-atom Pd1/PCN with chemical scissors.…”
Section: Photochemical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced from Ref. [52] with permission from the American Chemical Society. Scheme for the construction of high-loading single-atom Pd1/PCN with chemical scissors.…”
Section: Photochemical Methodsmentioning
confidence: 99%
“…The catalyst showed a very low overpotential (around 50 mV) for HER and remarkable stability compared with Pt and reduced graphene oxide. Wang et al used Fe 3 O 4 nanocubes as the template and sources of Fe to synthesize Fe SACs by the method of in situ ligand carbonization to form superlattices, followed by acid etching and NH 3 activation, as shown in Figure 4B [52] . The obtained Fe SACs with welldispersed Fe atoms supported on the carbon framework substrate [Figure 4C] showed outstanding ORR properties in alkaline media and comparable zinc-air battery performance comparable to commercial Pt/C catalysts.…”
Section: Chemical Etchingmentioning
confidence: 99%
See 1 more Smart Citation
“…[129][130][131][132][133] To achieve the stable loading of SAM cocatalysts on CN with high dispersion, diverse methods such as ligand decoration and interlaminar bridged site construction have been adopted with great improvements. 131,[134][135][136] For example, boron-oxo species can be highly dispersed on CN via a boric-acid-mediated route due to dative B-N coordination and prove to be effective mediators for anchoring transition metal (Ni, Co, Fe) atoms. 85,97 According to the report of Wang et al, Ni single atoms were anchored by boron-oxo species on g-C 3 N 4 via a facile ion exchange strategy (Fig.…”
Section: Theoretical Calculations On Carbon Nitride-based Photocataly...mentioning
confidence: 99%
“…Recently, single-atom adsorption has become a high-profile technology for enhancing catalysis performance. 9,10 The adsorption of single metal atoms on 2D materials may also bring unique and interesting properties, such as magnetism, 11 enhanced magnetic anisotropy, 12 semiconductor−metal transition, 13 and multiferroicity. 14 In our previous work, 15 we also found that single Li atom doping could induce multiferroicity in a transition metal halide monolayer (i.e., CrBr 3 ).…”
Section: ■ Introductionmentioning
confidence: 99%